The Influence of Store Atmosphere, Price Perceptions, and Service Quality on Customer Satisfaction at Kedai Semoga Sukses - Cantika Eva Dialoka; Ugy Soebiantoro (International Journal of Economics (IJEC), 2024)
The purpose of this study was to determine the effect of Store Atmosphere, Price Perception, and Service Quality on Consumer Satisfaction at Kedai Selamat Sukses. This research method uses quantitative research, where the dependent variable is customer satisfaction and the independent variables are store atmosphere, price perception, and service quality. The population in this study are consumers who have visited and made purchases at Kedai Selamat Sukses. The number of samples taken was 108 respondents. Sampling using non-probability sampling method with purposive sampling technique. This research analysis technique uses the partial least squares (PLS) method. The results of this research analysis are: 1) Store Atmosphere influences customer satisfaction at Kedai Selamat Sukses, 2) Price Perception influences customer satisfaction at Kedai Selamat Sukses, 3) Service Quality influences customer satisfaction at Kedai Selamat Sukses.